Microglial changes dynamics in perifocal critical zones of progressing brain infarction. - Shuliatnikova, T. V.; Shavrin, V. O.; Шулятнікова, Тетяна Володимирівна; Шаврін, Володимир Олександрович (Запорізький державний медичний університет, 2018)
Introduction. From the first minutes of its formation and during the first week the focus of brain infarction is surrounded by a territory with critical characteristics of blood supply and functional state of the tissue, which is largely identical to the clinical concept of "ischemic penumbra". It is known that neuroglial reaction plays a huge role in the processes of adaptation and repair of damaged nervous tissue in many neuropathological processes. In the course of ischemic damage to the brain tissue the microglia reaction is one of the most significant. For better understanding of the reparative characteristics of the neural tissue in the process of progression of the infarction, a more detailed study of the microglia reactions to ischemic damage is necessary. The aim: To determine the dynamics of pathomorphological changes in microglia in perifocal critical zones of a progressive cerebral infarction. Material and methods: 40 sectional cases of hemispheric progressive cerebral infarction in the middle cerebral artery blood supply pool were used. In each case, 4 pieces of tissue were taken from zone bordering the nucleus of the infarct, and 2, 5 and 7 cm from the edge of the necrosis. Pieces were fixed in 10% formalin, embedded in paraffin, sections 5 microns thick were stained with hematoxylin-eosin, and Ortega’s impregnational detection of microglia by silver was used by. Sections were studied in an Axioplan 2 microscope ("Carl Zeiss", Germany).
Keywords: тези доповідей